Algerian Energy Policy After 2020: Comparative Swot Analysis For Promoting Renewable Energy And Shale Gas: Priorities, Opportunities And Challenges - Ghandir, Hatem; Siagh, Ahmed Ramzi (جامعة الوادي - University of Eloued, 2020)
The aim of this study is to examine the challenges and opportunities available in the field of new energies in Algeria, whether renewable energies or shale gas as an unconventional source of energy, these two energy fields are new in terms of investment and management in the country, which posed legislative, technological and financial challenges. On this basis, Algeria has approved a program for energy transition1 aimed at promoting the use of renewable energies, in order to avoid energy deficit. Therefore, according to the current “laissez-faire” scenario in terms of production and consumption, by 2030 the country may become unable to export, and then to an energy-importing country by 2040. Although the exploitation of shale gas in Algeria remains a matter governed by environmental, technical and financial challenges, but it represents an important bet for the country to enhance its energy and economic position. A SWOT analysis framework for a comparative analysis was applies to find out the various opportunities and challenges when exploiting renewable energy sources and shale gas, or when comparing these two sources in terms of economic and energy importance. The energy transition and exploiting different types of energy sources is no longer optional for Algeria, as the internal changes related to the decline in the national reserves of oil and gas and the increase in domestic demand. As well as external variables have pressed the Algerian decision-maker to respond to these changes. But it seems that what has been achieved so far in implementing renewable energy programs is very modest.
مقال
Keywords: Energy transition ; energy production scenario ; renewable energy ; shale gas ; Algeria